Adjustment of friction by duplex-treated, bionic structures for Sheet-Bulk Metal Forming. (July 2017) - Tillmann, Wolfgang; Stangier, Dominic; Lopes-Dias, Nelson-Filipe; Biermann, Dirk; Krebs, Eugen
Abstract: Bionic structures were applied on hardened AISI M3:2 and duplex-treated by means of plasmanitriding. Subsequently, a thin hard CrAlN coating was deposited on the substrate. The tribological properties of the structure systems were investigated in the full contact area, using identical friction partners (steel DP 600) of the forming process. The tribological behavior was analyzed in fundamental laboratory tests, using a modified tribometer and subsequently evaluated in application-orientated adapted ring-compression tests. Bionic structures are suitable to locally adjust the friction condition and proved to be an appropriate method to control the material flow of sheet metals in bulk forming operations. However, process related micro burrs lead to a roughness increase during subsequent treatments, thus increasing the friction and adhesive effects. Highlights: Bionic structures are produced by micromilling and plasmanitriding. CrAlN thin films protect structural patterns against plastic deformation. Bionic structures are able to adjust the friction properties. The anisotropy of the structures allows to compensate anisotropic material behavior.